Healthcare Information Technology Infrastructures in Turkey - Dogac, A. (Yearb Med Inform, 2014)
OBJECTIVES: The objective of this paper is to describe some of the major healthcare information technology (IT) infrastructures in Turkey, namely, Sağlık-Net (Turkish for “Health-Net”), the Centralized Hospital Appointment System, the Basic Health Statistics Module, the Core Resources Management System, and the e-prescription system of the Social Security Institution. International collaboration projects that are integrated with Sağlık-Net are also briefly summarized. METHODS: The authors provide a survey of the some of the major healthcare IT infrastructures in Turkey. RESULTS: Sağlık-Net has two main components: the National Health Information System (NHIS) and the Family Medicine Information System (FMIS). The NHIS is a nation-wide infrastructure for sharing patients’ Electronic Health Records (EHRs). So far, EHRs of 78.9 million people have been created in the NHIS. Similarly, family medicine is operational in the whole country via FMIS. Centralized Hospital Appointment System enables the citizens to easily make appointments in healthcare providers. Basic Health Statistics Module is used for collecting information about the health status, risks and indicators across the country. Core Resources Management System speeds up the flow of information between the headquarters and Provincial Health Directorates. The e-prescription system is linked with Sağlık-Net and seamlessly integrated with the healthcare provider information systems. Finally, Turkey is involved in several international projects for experience sharing and disseminating national developments. CONCLUSION: With the introduction of the “Health Transformation Program” in 2003, a number of successful healthcare IT infrastructures have been developed in Turkey. Currently, work is going on to enhance and further improve their functionality.